Edukasi Perilaku Hidup Bersih Dan Sehat Pada masyarakat Jalan Gedang RT.04 Kota Bengkulu - Made Rahayu N; Ein Kurnisa; Dini Pratiwi; Inge Anggraeni; Fery Surahman (Jurnal Dehasen Mengabdi, 2026)
This Community Service Program (KKN) was conducted to enhance the understanding and practice of Clean and Healthy Living Behavior (PHBS) among the residents of Jalan Gedang RT.04, Bengkulu City. The program focused on delivering health education through counseling sessions, demonstrations of proper handwashing with soap (CTPS), distribution of informational leaflets, and environmental observation. Evaluation was carried out using pre-test and post-test assessments to measure changes in knowledge and behavior. The results showed an approximate 30% increase in community knowledge, improved handwashing habits, and initial implementation of better household waste management practices. In addition, residents demonstrated increased enthusiasm for routine health check-ups. Overall, this program effectively encouraged positive health behavior changes and strengthened community awareness regarding the importance of maintaining clean and healthy living practices.